Ludo Integer Sebagai Pengembangan Media Pembelajaran Operasi Aritmatika Dasar Bilangan Bulat - Ria Octa Vioni; Aan Nurfahrudianto; Aprilia Dwi Handayani; Jatmiko (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
Ludo Integer is a development of learning media that innovates the game Ludo King into an education game. This media was developed to support students' learning on basic arithmetic operations on integers. This research purposeful to develop Ludo Integer learning media for VII class students of SMP Karya Wates. The research used method Research and Development (R&D) with ADDDIE development model comprise of Analysis, Design, Development, Implementation, and Evaluation. The analysis phase, researchers analyzing problems and supporting student learning needs. The Design phase, researchers designing the necessary media components and questionnaires. The Development phase, researchers is the media production that has been designed and then validated after all components of media finished. The Implementation phase, researchers conducting limited class trials and extensive class trials. The Evaluation phase, researchers processing research results and interpreting the feasibility of this media. Data collection techniques using questionnaires and student learning outcomes with pretest and posttest. This research was do at Karya Wates Middle School with a total of 13 students in class VII. Based on the average value of the validation test results obtained a value of 87.33 with a very good category used without revision. Practical media based on the practicality test obtained an average value of 88.61. Based on the effective media effectiveness test, the average value of posttest > pretest is 75.92 > 42.46. Keyword: ADDIE Models, Basic Arithmetic Operations on Integers, Ludo Integer